Reproducibility of Bruch Membrane Opening-Minimum Rim Width Measurements With Spectral Domain Optical Coherence Tomography. Issue 11 (November 2017) - Park, Keunheung; Kim, Jinmi; Lee, Jiwoong
Abstract : Purpose: To evaluate the reproducibility of Bruch membrane opening-minimum rim width (BMO-MRW) measurements obtained with Spectralis optical coherence tomography (OCT) in normal and glaucoma subjects. Materials and Methods: In total, 123 eyes from 123 subjects (65 healthy, 58 glaucoma subjects) were included. BMO-MRW measurements were repeated 3 times during the same visit using Spectralis OCT. The BMO points and internal limiting membrane were identified with automated software and corrected manually when necessary. The intravisit repeatability, coefficient of variation (CV), and intraclass correlation coefficient were analyzed for each sector and global BMO-MRW. The Spearman rank correlation coefficient was used to estimate correlations between CV and multiple variables. Multiple linear regression analysis was used to identify significant associations. Results: The intravisit repeatability ranged from 2.97 μm (global) to 10.25 μm (inferotemporal sector) in healthy subjects and from 3.31 μm (global) to 12.09 μm (inferonasal sector) in glaucoma subjects. The CVs ranged from 1.17% (global) to 3.56% (inferotemporal sector) in healthy subjects and from 2.57% (global) to 6.46% (superotemporal and inferotemporal sector) in glaucoma subjects. Intraclass correlation coefficients ranged from 0.974 (superotemporal sector) to 0.997 (nasal sector) in normal subjects and from 0.988 (temporal sector) to 0.997 (global and nasal sector) in glaucoma subjects. Multiple regression analysis showed that the CV in global BMO-MRW measurements was inversely associated with global BMO-MRW and visual field mean deviation ( P =0.001 and 0.002, respectively). Conclusions: The Spectralis SD-OCT showed excellent reproducibility in BMO-MRW measurements in both normal and glaucoma subjects. The measurements variability was worse in more advanced glaucoma.